Top-down LC–MS quantitation of intact denatured and native monoclonal antibodies in biological samples. (28th June 2018) - Zhang, Liyun; Vasicek, Lisa A; Hsieh, SuChun; Zhang, Shuli; Bateman, Kevin P; Henion, Jack
Aim: The requirements for developing antibody biotherapeutics benefit from understanding the nature and relevant aspects of the entire molecule. The method presented herein employs on-line multidimensional LC–quadrupole time-of-flight (QTOF)-MS for the quantitative determination of an antibody isolated from biological samples while maintaining the intact native biologically active conformation of the antibody.Results: Following method optimization for a model antibody, an incurred biotherapeutic in cynomologus monkey was quantified in its intact top-down native conformation. A partial method validation demonstrated acceptable precision and accuracy although improved sensitivity requires further studies.Conclusion: An on-line multidimensional LC–MS approach presents a proof-of-principle example for quantifying an intact, native antibody isolated from an incurred biological sample via immunoaffinity techniques coupled with top-down QTOF LC–MS bioanalysis.